GAMBARAN TINGKAT PENGETAHUAN IBU HAMIL TENTANG PERSALINAN OPERASI CAESAR DENGAN METODE ERACS - Fitri Eka Widyasari, - (2022)
The Indonesian Midwives Association (IBI) in Sumedang Regency predicts that the pregnancy rate will continue to increase. According to data written at the Health Office, there were only 5,302 pregnant women in 2020 and 17,942 in 2021. Pregnant women will experience physiological changes that result in a decrease in partial immunity during pregnancy. It does not rule out the possibility that if something happens that makes the safety of the mother and the prospective baby not good, it must be done with sectio cassarea (SC) surgery. In Sumedang Regency, there is a method that can minimize pain and infection due to postoperative sectio cassarea (SC) at an affordable cost, namely using the eracs method. This study aims to determine the knowledge of pregnant women about caesarean section. The population and samples taken by total sampling are pregnant women who have undergone caesarean section by dr. Dinny Sri Utami, Sp.OG, M, Kes as many as 35 people. The research instrument used a questionnaire. Quantitative data analysis was carried out using a frequency distribution table. The results showed that the level of knowledge of pregnant women about caesarean section method mostly had less knowledge as many as 19 people (54.3%). While pregnant women who have sufficient knowledge are 11 people (31.4%) and those who have good knowledge are 5 people (14.3%). It can be concluded that the level of knowledge of pregnant women about caesarean section in Sumedang Regency is still lacking. It is hoped that health workers such as midwives and obstetricians will better educate pregnant women.